Low-molecular-weight heparin in addition to low-dose aspirin for preventing preeclampsia and its complications: A systematic review and meta-analysis - Zheng, Li; Xia, Binbin; Yuan, Yuan; Wang, Yuran; Wang, Yan (Frontiers in Cardiovascular Medicine, 2022)
Background: In this systematic review, we aimed to investigate the efficacy and safety of adding low-molecular-weight heparin (LMWH) or unfractionated heparin to low-dose aspirin (LDA) started≤16 weeks’ gestation in the prevention of pre-eclampsia (PE) in high-risk women. Methods: PubMed, Cochrane Library, Embase, and ClinicalTrials.gov databases were searched from their inception to October 2021 for randomised controlled trials (RCTs) that to determine whether the combined treatment of LMWH and LDA is better than single anticoagulant drugs in preventing PE and improving live birth rate of fetus in high-risk women with pregnancy≤16 weeks. We also searched Embase, OVID MEDLINE and OVID MEDLINE in-process using the OVID platform. Results: 14 RCTs involving 1912 weman were found. 952 randomly assigned to LMWH (or unfractionated heparin) and LDA group and 960 randomly assigned to aspirin group. The meta-analysis showed that the addition of LMWH to low-dose aspirin reduced the risk of PE (OR: 0.54, 95% CI: 0.38-0.76, P＜0.05), SGA (OR: 0.66, 95% CI: 0.45-0.97, P=0.03) , foetal and neonatal death (OR: 0.43, 95% CI: 0.22-0.87, P=0.02) and gestational hypertension (OR: 0.42, 95% CI: 0.20-0.89, P=0.02). It is worth emphasizing that LMWH (or unfractionated heparin) combined with LDA did not increase the risk of bleeding. Conclusions: LMWH combined with LDA can effectively improve the pregnancy outcome of women with high risk factors for PE and its complications. Although this study showed that combined medication also did not increase the risk of bleeding, but such results lack the support of large sample size studies. The clinical safety analysis of LMWH combined with LDA in patients with preeclampsia should be more carried out.